The impact of splinting mobile mandibular incisors on oral health-related quality of Life: preliminary observations from a randomized clinical trial - Sonnenschein, Sarah K.; Ziegler, Philipp; Ciardo, Antonio; Rütters, Maurice; Krisam, Johannes; Kim, Ti-Sun (Journal of clinical periodontology, 2021)
Aim To compare the Oral Health-Related Quality of Life (OHRQoL) of patients with mobile mandibular incisors before and after full-mouth disinfection (FMD) with and without splinting. Material and methods Thirty-four periodontitis patients with ≥1 mobile mandibular incisor (degree II/III) were randomly allocated to the test or control group. All patients received FMD and the test group additional splinting of teeth 33-43. OHRQoL was assessed before (BL) and 3 months after FMD (RE) using the Oral Health Impact Profile (OHIP)-14. Data were compared within and between the groups (Wilcoxon test/Mann-Whitney U test). Results Twenty-eight patients (13 test group/15 control group) were re-evaluated. FMD led to a reduction of the mean probing pocket depth (PPD; in mm) (test group: BL-PPD 3.89 ± 1.03, RE-PPD 2.82 ± 0.53; control group: BL-PPD 3.58 ± 0.66, RE-PPD 2.77 ± 0.59; each p ≤ .001), the mean clinical attachment level (CAL; in mm) (test group: BL-CAL 5.22 ± 1.38, RE-CAL 4.79 ± 0.85; control group: BL-CAL 4.58 ± 1.10, RE-CAL 4.41 ± 0.96; each p ≤ .05), and the mean OHIP-14 summary scores (test group: BL-OHIP 21.7 ± 11.06, RE-OHIP 9.9 ± 8.96, p = .0046; control group: BL-OHIP 16.8 ± 8.27, RE-OHIP 11.7 ± 8.55; p = .0217). The reduction of the OHIP-G14 scores was considerably higher in the test group but statistically not significant (p = .080). Conclusions The results show a positive impact of non-surgical periodontal treatment on OHRQoL and a possible tendency for further improvement by splinting mobile mandibular incisors.
Gesehen am 05.09.2023